Indoor radiowave propagation prediction and measurement for indoor geolocation system using WLAN - Ismail, Abdul Hafiizh (2005)
Propagation prediction and measurement plays an important role in the design and implementation of indoor geolocation system In this project, a three-dimensional (3D) ray tracing technique-Site Specific Outdoor / Indoor Propagation Prediction Code will be used to predict indoor propagation effects in Wireless Communication Centre (WCC), Fakulti Kejuruteraan Elektrik, University Technology Malaysia. Propagation prediction will be done of signal strength using Airmagnet software will be carried out within the research area.